2018
DOI: 10.1007/s11065-018-9374-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effects of Computerized Cognitive Training on Executive Functions: a Cross-Disciplinary Taxonomy for Classifying Outcome Cognitive Factors

Abstract: The growing prevalence of neurodegenerative disorders associated with aging and cognitive decline has generated increasing cross-disciplinary interest in non-pharmacological interventions, such as computerized cognitive training (CCT), which may prevent or slow cognitive decline. However, inconsistent findings across meta-analytic reviews in the field suggest a lack of cross-disciplinary consensus and on-going debate regarding the benefits of CCT. We posit that a contributing factor is the lack of a theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 71 publications
0
89
2
1
Order By: Relevance
“…In our study, we did not find a significant difference between computerized and non-computerized training. Although the average effect of the computerized training was higher than in the work of Webb et al (2018) (current study = 0.281; Webb = 0.17), we found a non-significant (p = 0.10) higher benefit for noncomputerized training (g = 0.373). Therefore, as underlined by Diamond and Ling (2016), computerized training probably could be effective only for the Inhibition component of EFs.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In our study, we did not find a significant difference between computerized and non-computerized training. Although the average effect of the computerized training was higher than in the work of Webb et al (2018) (current study = 0.281; Webb = 0.17), we found a non-significant (p = 0.10) higher benefit for noncomputerized training (g = 0.373). Therefore, as underlined by Diamond and Ling (2016), computerized training probably could be effective only for the Inhibition component of EFs.…”
Section: Discussioncontrasting
confidence: 77%
“…As Martinovic et al (2016) demonstrated, videogames are engaging if they are simple and rewarding, but they are not motivating if they ask the children to improve their attention and problem-solving skills. Moreover, in their meta-analysis concerning computerized EF training programs, Webb et al (2018) found a small effect on the three EF factors (Inhibition, Updating, and Shifting): Hedges' g effect size ranged from 0.005 (Updating) to 0.16-0.17 (Shifting and Inhibition). It is important to note, however, that Webb et al (2018) analyzed a large sample of participants, mostly older adults, probably not very familiar to work with a computer: For this reason, they are, most probably, not the best target for a computerized training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome will be overall cognitive performance, de ned as the mean effect size across all cognitive outcomes in a study [10,13,14,22]. Secondary outcomes are domain-speci c cognitive performance, classi ed according to the CHC-M framework [24], global cognition, subjective cognition, mood, other psychiatric symptoms, psychosocial functioning and daily function.…”
Section: Types Of Outcomesmentioning
confidence: 99%
“… 12 15–17 A promising approach to foster empirically valid insights into any association between cognition and tinnitus is through evaluating and categorising tests of cognitive performance according to the theoretical constructs that they are thought to measure. 20 Webb et al 21 describe a cross-disciplinary taxonomy for categorising cognitive performance measures (Cattell-Horn-Carroll-Miyake or CHC-M)). This features combined CHC and Miyake theoretical elements 22 23 and includes a comprehensive taxonomical categorisation of cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%